The nutritional levels and status of vitamins among children in Henan, China - Li, Xiaojuan; Chen, Nan; Guo, Lei; Luan, Yusheng; Jin, Zhipeng; Yang, Junmei; Li, Tiewei (Frontiers in Nutrition, 2025)
BackgroundVitamins are vital for children’s health, and deficiencies can cause disorders, compromising quality of life and survival. This study systematically assesses multivitamin levels, nutritional status, and associated factors in children from Henan, China. It aims to provide robust evidence to improve pediatric nutrition and inform policies for local governments and institutions.MethodsThis retrospective study analyzed data from 1,995 healthy children who underwent routine physical examinations between March 1, 2022, and May 20, 2024. General clinical information and vitamin test results, including vitamins A, D, B1, B2, B3, B5, B7, and C, were retrieved from electronic medical records. Participants were categorized into four age groups: under 3 years, 3–5 years, 6–11 years and 12–18 years. Seasonal classification comprised spring, summer, autumn, and winter.ResultsThe cohort consisted of 1,185 males and 810 females. Age distribution included 248 children under 3 years, 743 children aged 3 to 5 years, 883 children aged 6 to 11 years and 121 children aged 12 years or older. Analysis of vitamin insufficiency revealed the highest insufficiency rates for vitamin B7 (58.8%), followed by vitamin D (28.5%), A (28.0%), B1 (11.8%), C (9.1%), E (2.2%), and B3 (0.1%). Notable sex-specific differences were identified in vitamin D, E, B2, B5, and C levels. Age-dependent variations were observed for vitamin A, D, E, B1, B2, B3, B5, B7, and C, while seasonal fluctuations impacted vitamin A, D, E, B1, B3, B5, B7, and C. Sex-based analysis indicated a higher prevalence of vitamin A and C insufficiencies in males and a greater incidence of vitamin D insufficiency in females. Preschool children exhibited the highest vitamin A insufficiency rates, whereas adolescent aged children demonstrated the highest insufficiencies in vitamin D, E, B1, B7, and C. Seasonal analysis revealed increased vitamin A and C insufficiencies during summer, heightened vitamin D and B7 insufficiencies in winter, vitamin E insufficiencies in spring, and vitamin B1 deficiencies in autumn.ConclusionA high prevalence of vitamin insufficiencies, particularly in vitamins B7, D, A, and C, was observed among children in Henan, China, with variation rates associated with sex, age, and season.